Condolence strategy used by Facebook user to respond obituary news - Al-Manduriy, Shahibul Muttaqien (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
Technology has changed the world of human communication today. News, information, and issues are delivered through technological advances with incredible speed. Social media such as Facebook are one of many technology mediators used by the people in the world to share information. This information can be in many forms, such as personal information, selling information, obituary information and etc. Obituary information is shared by the people on Facebook and responded to by other people with various responses. This study is descriptive research to find the strategy used by people in the Indonesian context while responding to the obituary updated on Facebook. The subjects are lecturer’s wife, artist, and an abortion girl. This study has described the responses from Facebook users as the strategy in responding to the obituary. The finding of this study showed that the condolence strategy used always depends on the person who dies itself. The person who is seen as the good person will have a good response, while someone who is seen as a bad person, in this case, the girl who did an abortion, has a positive and negative response.